2020
DOI: 10.3390/md18100502
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Extraction and Antioxidant Capacity of Mycosporine-Like Amino Acids from Red Alga Dulse Palmaria palmata in Japan

Abstract: Mycosporine-like amino acids (MAAs) are the ultraviolet (UV)-absorbable compounds, which are naturally produced by cyanobacteria and algae. Not only these algae but also marine organisms utilize MAAs to protect their DNA from UV-induced damage. On the other hand, the content of MAAs in algae was changed by the environmental condition and season. In addition to the UV-protected function, the antioxidant capacity of MAAs can apply to the cosmetic sunscreen materials and anti-cancer for human health. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 68 publications
(126 reference statements)
2
32
0
Order By: Relevance
“…Regarding the total MAA concentrations, no differences between the two solvents were found but the highest MAA amounts were observed by injecting them directly in the HPLC. According to these results, distilled water could be an excellent extraction solvent for MAAs, as Nishida et al [ 33 ] concluded in the extraction of MAAs form Palmaria palmata . Nishida et al [ 33 ] applied a successive extraction method by using water and then methanol extraction, and spectrophotometric and HPLC analyses revealed that the yield of MAAs by 6 h water extraction was the highest among the tested conditions.…”
Section: Methodology For Extraction and Chemical Identification Ofmentioning
confidence: 96%
See 3 more Smart Citations
“…Regarding the total MAA concentrations, no differences between the two solvents were found but the highest MAA amounts were observed by injecting them directly in the HPLC. According to these results, distilled water could be an excellent extraction solvent for MAAs, as Nishida et al [ 33 ] concluded in the extraction of MAAs form Palmaria palmata . Nishida et al [ 33 ] applied a successive extraction method by using water and then methanol extraction, and spectrophotometric and HPLC analyses revealed that the yield of MAAs by 6 h water extraction was the highest among the tested conditions.…”
Section: Methodology For Extraction and Chemical Identification Ofmentioning
confidence: 96%
“…According to these results, distilled water could be an excellent extraction solvent for MAAs, as Nishida et al [ 33 ] concluded in the extraction of MAAs form Palmaria palmata . Nishida et al [ 33 ] applied a successive extraction method by using water and then methanol extraction, and spectrophotometric and HPLC analyses revealed that the yield of MAAs by 6 h water extraction was the highest among the tested conditions. Nevertheless, according to Chaves-Peña et al [ 32 ] the re-dissolution in pure methanol after dryness was the best option for the qualitative analysis of the most common MAAs in red algae in contrast to those reported by Karsten et al [ 31 ].…”
Section: Methodology For Extraction and Chemical Identification Ofmentioning
confidence: 96%
See 2 more Smart Citations
“…Sunscreen formulations containing mixtures of secondary metabolites from plants, algae, and fungi, as well as from cyanobacteria [ 40 ], showed a higher shielding effect with respect to commercial filters. In addition, mycosporins and mycosporin-like amino acids (MAAs) [ 41 ] produced by marine phototrophs (dinoflagellates, cyanobacteria, and macro algae) [ 42 ] are able to convert radiative energy in thermal energy without generation of radical species [ 43 ]. Sunscreen formulations containing MAAs from Porphyra umbilicals showed a high protective effect on fibroblasts and keratinocytes exposed to UV-A [ 44 ].…”
Section: Introductionmentioning
confidence: 99%